THE USE AND RESULTS OF THE CLIL METHOD IN UZBEK SCHOOLS - Shamsiddinova Gulkhumor Asliddin kizi (International Journal of Literature and Language Studies, 2026)
This article examines the implementation and impact of the Content and Language Integrated Learning (CLIL) methodology within the secondary and primary education sectors of Uzbekistan. Drawing on recent pedagogical research and case studies from local schools, the study highlights how teaching subjects like art, science, or history through a foreign language (primarily English) enhances students' communicative competence and cognitive flexibility. The findings reveal a generally positive attitude among learners, with improved motivation and natural language acquisition through context-based learning. However, the article also identifies significant barriers to broader success, including the urgent need for specialized teacher training, the development of context-sensitive materials, and institutional support to overcome linguistic gaps between students and subject matter.